Determination of CAR T cell metabolism in an optimized protocol - Joaquina, Sandy; Forcados, Christopher; Caulier, Benjamin; Inderberg, Else Marit; Wälchli, Sébastien (Frontiers in Bioengineering and Biotechnology, 2023)
Adoptive transfer of T cells modified to express chimeric antigenic receptors (CAR) has emerged as a solution to cure refractory malignancies. However, although haematological cancers are now well treated by CAR T cells, solid tumours have been more challenging to control. The later type is somehow protected by a strong tumour microenvironment (TME) which might impact cellular therapeutic treatments. Indeed, the milieu around the tumour becomes particularly inhibitory to T cells by directly affecting their metabolism. Consequently, the therapeutic cells become physically impeded before being able to attack the tumour. It is therefore extremely important to understand the mechanism behind this metabolic break in order to develop TME-resistant CAR T cells. Historically, the measurement of cellular metabolism has been performed at a low throughput which only permitted a limited number of measurements. However, this has been changed by the introduction of real-time technologies which have lately become more popular to study CAR T cell quality. Unfortunately, the published protocols lack uniformity and their interpretation become confusing. We herein tested the essential parameters to perform a metabolic study on CAR T cells and propose a check list of factors that should be set in order to draw sound conclusions.